Design concept and parameters of a conical bar separator - Jadwisieńczak, Beata; Kaliniewicz, Zdzisław (Technical Sciences, 2017)
The process of adapting a screen separator to seeds of a given species and variety requires a corresponding set of replaceable screens. Screen replacement is a time-consuming process. Screens are often selected from the available size range, therefore, cleaning and separation processes are not always optimized. This study proposes a design concept of a new device for cleaning and separating seeds, which features a conical bar screen that rotates around its own axis. The screen has grooves whose width is smallest at the beginning of the screen and increases along the screen surface. Seeds can be sorted into various size fractions by changing the position of collecting buckets under the screen. The functional parameters of the separating device were designed based on a review of publications describing the size of the most popular agricultural seeds. The basic geometrical relationships in the proposed conical bar screen were described. The geometrical parameters of the screen were selected on the assumption that the radius at which bars are fixed to the screen can range from 200 mm to 400 mm and that bar diameter can range from 5 mm to 10 mm. Two variants of the device were proposed as a replacement for one universal separating screen. The first variant will be used to sort small seeds, including seeds of small-seeded legumes, seeds of major cereal species and medium-sized seeds with dimensions similar to cereal seeds, whereas the second variant will be applied to separate large seeds, including seeds of large-seeded legumes and plumper seeds from the medium-size fraction. The width of grooves at the beginning and end of the screen should equal 1 mm and 5 mm in the first variant and 2.5 mm and 13 mm in the second variant, respectively.